2019
DOI: 10.3832/ifor2883-012
|View full text |Cite
|
Sign up to set email alerts
|

Hemlock woolly adelgid niche models from the invasive eastern North American range with projections to native ranges and future climates

Abstract: The hemlock woolly adelgid (Adelges tsugae Annand-HWA) is invasive in eastern North America where it causes extensive mortality to hemlock communities. The future of these communities under projected climate change is an issue of landscape ecological interest and speculation. We employed the MaxEnt algorithm with the random subset feature selection algorithm (RSFSA) in creating HWA niche models. Final models were ensembles of 12 statistically best models with six predictors each. Out of 119 climatic, topograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…WorldClim indices (Bradie and Leung 2016), including the SuppClim and AET/PET indices, supporting our previous ndings (Tracy et al 2018(Tracy et al , 2019Kantola et al 2019b). This is the rst study to nd that soil taxa are important variables for niche modeling of milkweeds, with soil taxa variables highly ranked in niche models of all four South-Central US species.…”
Section: Niche Modelingsupporting
confidence: 82%
See 2 more Smart Citations
“…WorldClim indices (Bradie and Leung 2016), including the SuppClim and AET/PET indices, supporting our previous ndings (Tracy et al 2018(Tracy et al , 2019Kantola et al 2019b). This is the rst study to nd that soil taxa are important variables for niche modeling of milkweeds, with soil taxa variables highly ranked in niche models of all four South-Central US species.…”
Section: Niche Modelingsupporting
confidence: 82%
“…The RSFSA revealed that subsets of six to eight of 95 variables were optimal for maximizing performance of MaxEnt models of the four milkweed species. Tracy et al (2019) and Kantola et al (2019b) also found that six and eight variables was an optimal subset size for MaxEnt models using RSFSA with large sets of 80 and 119 variables, respectively. Consistent with previous niche modeling studies using RSFSA, we found signi cantly improved values of AUC psa and AICc bg for selected models over random models, but over tting was only sometimes improved (Tracy et al 2018(Tracy et al , 2019Kantola et al 2019b).…”
Section: Niche Modelingmentioning
confidence: 90%
See 1 more Smart Citation
“…The HWA does not appear to harm hemlock species within its native range of Asia and northwestern North America (Oten et al, 2014). However, in the mid 20th century, the HWA arrived in the eastern United States (USA) with the introduction of ornamental hemlocks, and it has since spread from northern Georgia to southern Nova Scotia (Kantola et al, 2019). Hemlock loss can have ecosystem-level effects owing to their foundational role in some eastern mixed hardwood forests.…”
Section: Introductionmentioning
confidence: 99%
“…A strategy developed to select appropriate sites for the natural enemy’s liberation based on prioritizing its environmental requirements could increase the success of biological control agents [ 32 ]. Ecological niche modeling is a tool widely used for estimating environmental suitability for organisms, building ecological models for successful prediction in specific geographic areas of interest [ 33 , 34 , 35 , 36 ]. In this study, we calculated the ecological niche model for A. opuntiarum and C. cactorum to define regions of environmental suitability and determine niche overlap for the purpose of predicting areas of successful establishment of this parasitoid in North America.…”
Section: Introductionmentioning
confidence: 99%